Online Field Current Estimation for Brushless Synchronous Starter/Generator Considering the Rectifier Commutation Mode - Ji Pang; Feihang Zhou; Jianwei Yang; Weiyi Zhang; Youming Wang; Weiguo Liu; Ningfei Jiao (CES Transactions on Electrical Machines and Systems)
The information of the field current is essential for the brushless synchronous starter/generator system, which determines the performance and health status of this system. However, since the field winding of the main machine is installed in the rotor part, the measurement of the field current in this brushless system seem impossible. Considering that, the field current might be affected by the rectifier mode, the field current estimation method in different rectifier mode is studied in this paper. The main exciter (ME) rotor currents were restructured based on the ME flux equations. With these restructured rotor currents, the field current in different rectifier commutation mode is analyzed, then the field current estimation method considering the rectifier mode can be obtained. The experiments in different rectifier modes are carried out to verify the proposed method.